(untitled) (Medical Forum Monthly, 2024)
Objective: To reaffirm the importance of cadaveric dissection and prosected specimens in imparting knowledge of Anatomy to medical students from the perspective of faculty of anatomy. Study Design: Cross sectional study Place and Duration of Study: This study was carried out in the Anatomy Department of Fazaia Medical College, Islamabad from January 2016 to March 2016. Materials and Methods: Data was collected from100 faculty members working in the Anatomy department of medical colleges of Rawalpindi and Islamabad having at least 2 years of teaching experience. Results: In spite of facing certain limitations, 60 % of the faculty considered cadaveric dissection as an indispensable tool for teaching Anatomy while 70% of the participants were of the view that combination of dissection and prosection is the best technique. Conclusion: The importance of traditional teaching methods in imparting knowledge of Anatomy cannot be undermined.